PENGGUNAAN ZINE SEBAGAI MEDIA PENGENALAN STAGE OF GRIEF KEPADA REMAJA - Frederick Argindo; Riama Maslan Sihombing (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
There are various response and reaction when someone is facing grief. Most of the people who went through it, will experience the Stage of Grief. The theory of Stage of Grief is still unusual to some people because the lack of literacy about related theory, especially for teenagers. Another factor that takes effect is teenager’s reading interest. Nowadays, zine is a visual media that is appealing and effective enough for the young readers. This research will study some literacy that contains Stage of Grief theory using the qualitative descriptive method. Based on the theories that are used (Stage of Grief theory, theory about effects of visual elements on reading interest, and theory about zine), a conclusion was made that zine is an appropriate literacy choice for young readers, where the text and illustration have a balanced proportion. Zine as a visual media is enough to make the readers to understand the contents easier.